O papel das energias renováveis no processo de transição energética do estado de minas gerais: modelagem de sistemas energéticos para o horizonte 2030-2050 - Morjana Moreira Dos Anjos (2019)
It is widely known that development is connected to energy consumption, and this dependence, associated with population growth and the expansion of economic activities, consequently increases the demand for energy. Traditionally, the energy supply of most countries has been met by fossil fuels, but there are several problems associated with these sources and their production. In this way and considering the risks related to energy security and the challenges posed by climate change, thinking about energy alternatives to promote an energy transition seems to be reasonable. Thus, the present work carried out a modeling of the Minas Gerais energy system to subsidize an energy transition with a view to expanding renewable energies and promoting energy efficiency at the state and municipal levels, as well as combating climate change. Projections, in the 2030-2050 horizon, were made using the tool Long-range Energy Alternatives Planning System (LEAP) to establish a model of energy transition policy for Minas Gerais State. An effectiveness analysis of the state's main renewable energy policy, the Minas Gerais Renewable Energy Program (PMER, in Portuguese), was also made. The modeling considered key assumptions based on historical data of demographic and economic origin, which subsidized the elaboration of three scenarios. The first one is the Reference Scenario (REF), which considers what will happen if no additional energy policy is created. The two others are alternatives scenarios that incorporate the REF scenario and contemplates additional policies. Thus, the Moderate Energy Transition Scenarios (ETM) aims to contribute to the energy sector goals of the Brazilian Nationally-Determined Contributions – NDC, and the Advanced Energy Transition Scenarios (ETA) goes beyond of NDC's goals, being even more ambitious in terms of renewable energy and penetration of electric vehicles in the transportation sector. The analyzes have shown that current policies are not sufficient to promote the state transition to sustainable energy systems, and that this process will largely depend on the energy policies initiated and implemented in the near future. In the REF scenario, energy demand is expected to increase 55% by 2030, and this amount will almost triple by 2050. The electric matrix will be composed mostly of fossil fuels, 75%, by the end of the period analyzed. The ETM and ETA scenarios have proven to be viable options in terms of changing the future perspectives that are carbon intensive and costly, by implementing medium-long-term policies towards more sustainable energy systems. The ETA scenario presented the best cost-benefit ratio and was used to support the State Energy Transition Policy (PETE, in Portuguese), which proved to be a policy capable of guaranteeing a healthy environment with access to safe and reliable energy for all.